ANALISIS PENGARUH KURS, BI RATE DAN INFLASI TERHADAP IHSG DI BEI PERIODE 2014-2017 - Esty Nidianti; Edi Wijayanto (FInance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2019)
The aim of this study was to determine the effect of macro economic conditions which including the exchange rate, BI rate and inflation of the composite stock price index. The study had used quantitative approach. Determination of the sample was based on time series data periode January 2014 – December 2017 by using saturation sampling method, which resulted 48 as number of samples. This study also had chosen multiple linier regression as attempts to analyze data. The simultaneous test (F test) resulted that the exchange rate, BI rate, and inflation had given significant effect on the stock price index. Meanwhile, the partial test (t test) had indicated that the exchange rate variable and BI rate significantly influenced the stock price index. In contrast, rate of inflation had not showed significant effect on the stock price index.